Penerapan Buku Saku dengan Pendekatan Saintifik untuk Meningkatkan Motivasi dan Hasil Belajar Siswa Pasca Gempa Bumi - Nurhayati, Erlis (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2019)
The purpose of this study was to increase motivation and student learning outcomes after the earthquake in SMP Negeri 1 Gangga through the application of a Pocket Book with a scientific approach. The research method used was classroom action research consisting of 4 stages, namely planning, action implementation, observation and reflection. The research instruments used were observation sheets and tests. While the data of this research were analyzed through descriptive qualitative and qualitative analysis techniques. The results of the study showed that the application of a Pocket Book with a scientific approach had been able to increase motivation and student learning outcomes. This could be proved by data of all classroom action research activities which had showed improvements starting from pre-action, cycle 1 and cycle II.